2018
DOI: 10.3390/ijms19041112
|View full text |Cite
|
Sign up to set email alerts
|

Dandelion Root Extract Induces Intracellular Ca2+ Increases in HEK293 Cells

Abstract: Dandelion (Taraxacum officinale Weber ex F.H.Wigg.) has been used for centuries as an ethnomedical remedy. Nonetheless, the extensive use of different kinds of dandelion extracts and preparations is based on empirical findings. Some of the tissue-specific effects reported for diverse dandelion extracts may result from their action on intracellular signaling cascades. Therefore, the aim of this study was to evaluate the effects of an ethanolic dandelion root extract (DRE) on Ca2+ signaling in human embryonic ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
20
2
Order By: Relevance
“…The effect of DRE on ClC-Ka is mediated by the activation of PKC pathway. While dissecting the effect of DRE on Ca 2+ signaling, we demonstrated that DRE-induced Ca 2+ release from the ER is a consequence of the activation of the Gαq/PLC/IP3 pathway 18 suggesting the activation of the conventional PKC, referred downstream in this signaling cascade as follow: PLC splits phosphatidylinositol into IP3 and diacylglycerol (DAG), the latter involved in the activation of the membrane-bound PKC together with intracellular Ca 2+ 29 . To evaluate whether the effect of DRE on ClC-Ka was dependent to the activation of conventional PKC pathway, we performed DRE experiments in the presence of either the Ca 2+ chelator BAPTA or PKC inhibitor Calphostin C. As shown in Figure 3A, the inhibitory effect on ClC-Ka activity recorded after 20 min of exposure to 400 µg/mL DRE was abolished at each time point when the cells were treated with BAPTA.…”
Section: Dre Inhibits Also the Activity Of Clc-kb While Other Renal Tmentioning
confidence: 98%
See 2 more Smart Citations
“…The effect of DRE on ClC-Ka is mediated by the activation of PKC pathway. While dissecting the effect of DRE on Ca 2+ signaling, we demonstrated that DRE-induced Ca 2+ release from the ER is a consequence of the activation of the Gαq/PLC/IP3 pathway 18 suggesting the activation of the conventional PKC, referred downstream in this signaling cascade as follow: PLC splits phosphatidylinositol into IP3 and diacylglycerol (DAG), the latter involved in the activation of the membrane-bound PKC together with intracellular Ca 2+ 29 . To evaluate whether the effect of DRE on ClC-Ka was dependent to the activation of conventional PKC pathway, we performed DRE experiments in the presence of either the Ca 2+ chelator BAPTA or PKC inhibitor Calphostin C. As shown in Figure 3A, the inhibitory effect on ClC-Ka activity recorded after 20 min of exposure to 400 µg/mL DRE was abolished at each time point when the cells were treated with BAPTA.…”
Section: Dre Inhibits Also the Activity Of Clc-kb While Other Renal Tmentioning
confidence: 98%
“…For all the functional experiments we used a dose of DRE (400 µg/mL) that we previously characterized and tested in terms of maximal tolerated concentration and ability to mobilize intracellular Ca 2+ and activate phospholipase C (PLC) in HEK293 cells 18 . Figure 1A (Upper panel) reports representative Cl − currents recorded from the same ClC-Ka/barttin expressing HEK293 cell, at the start of the whole-cell recording, i.e.…”
Section: Dre Time-dependently Inhibits the CL − Current In Hek293 Celmentioning
confidence: 99%
See 1 more Smart Citation
“…Some specific components from plant extracts also have the ability to bind to protein domains, leading to modification or inhibition of enzymatic activities. It has been reported that dandelion root extracts dose-dependently increase intracellular Ca 2+ levels in HEK293 cells, partially by stimulating sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA) [37]. Chatterjee et al observed a rapid activation of caspase-8 enzyme in A375 cells when treated with dandelion root extracts for 30 min, pointing to the direct effects of dandelion root extracts on enzymatic activity but not gene transcription [38].…”
Section: Discussionmentioning
confidence: 99%
“…Its leaves are used in salads, and its roots are used as coffee 8 . It has lately been determined that some components of the plant are effective as diuretic, laxative, biliary deterrent, although the plant has usually been used as a cure for liver and gall disturbances since the ancient times 9 . Studies on the antioxidant 10 , anti-inflammatory 11 , antidiabetic 12 , antiulcer 13 , anti-rheumatic 14 , and anticancer 15 properties of T. officinale have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%